Associations of socioeconomic and other environmental factors with early brain development in Bangladeshi infants and children. (August 2021) - Jensen, Sarah K.G.; Xie, Wanze; Kumar, Swapna; Haque, Rashidul; Petri, William A.; Nelson, Charles A.
Highlights: Research from high-income countries shows that experiences impact neural development. We examine EEG in relation to wealth and psychosocial factors in 6 and 36-month-olds from Bangladesh. Wealth and maternal stress is associated with EEG oscillations in 36-month-olds. Neither wealth nor maternal stress is associated with EEG oscillations in 6-month-olds. Environmental influences on EEG may emerge between 6 and 36 months of age. Abstract: Studies of infants growing up in high-income countries reveal developmental changes in electroencephalography (EEG) power whereby socioeconomic factors - specifically, low SES and low income - are associated with lower EEG power in infants aged newborn to nine months. In the current paper we explore relationships of spectral EEG power across three regions (frontal, central, and parietal) and four frequency bands (theta, alpha, beta, and gamma) with socioeconomic and psychosocial factors in a cohort of n = 160 6-month-old infants and n = 187 36-month-old children living in Dhaka, Bangladesh. Household wealth is assessed as a multi-dimensional composite score encompassing income, assets, and housing materials. Psychosocial factors include maternal perceived stress and family caregiving activities. Among the 6-month-old infants we do not observe any association of household wealth or psychosocial factors with EEG power. Among the 36-month-old children, we find that household wealth is negatively associated absolute power in the beta and gamma bands across frontal, central, and parietal electrodes. We also find that higher reports of maternal perceived stress are associated with more absolute theta power in frontal and central regions in the 36-month-old children. The finding of a negative relationship of household wealth with beta and gamma power in 36-month-old children differs from findings previously observed in infants in high-income countries. Overall, findings suggest that children's environment continues to influence the development of EEG oscillations and provide support for the utility of EEG to quantify developmental effects of early life experiences on neural functional outcomes in low income countries.